Outcomes of free flap reconstructive surgery in head and neck cancer patients over 80-years old. Issue 9 (November 2021) - Mitchell, O.; Kelly, E.; Ethunandan, M.; Horlock, N.; Sharma, S.; Singh, R.P.
Abstract: An increasing elderly population in the United Kingdom has led to an increasing number of older patients with head and neck cancer, resulting in a greater demand for complex head and neck reconstructive surgery in this potentially high-risk age group. A possible perceived poorer tolerance to such major treatment risks under-treating some of these patients. The purpose of this study was to assess the outcomes in the elderly population (older than 80 years) who had undergone free flap reconstruction following head and neck cancer resection. A retrospective review of 127 patients was performed. Eighteen patients were 80 or older (14.2%) and 109 under 80 (85.8%). The elderly group experienced increased number of postoperative medical complications (p = 0.01), but the surgical complications were not significantly different in the two groups (p = 0.4). The average length of hospital stay was significantly longer in the older group (p = 0.01). There was one flap failure during the study period, which belonged to the younger group of patients. Elderly patients undergoing free flap reconstruction experience an increased rate of postoperative medical complications resulting in an increased length of hospital stay. However, good surgical outcomes can still be achieved in this age group, and therefore age alone should not be considered as a primary factor in head and neck cancer management.